Mohos ambientales fitopatógenos asociados a plantas maderables en bosques de terraza media del arboretum CIEFOR Puerto Almendras - Dávila Flores, Carlos Roberto (2023)
The present study allowed to evaluate the frequency of signs, symptoms, phytopathogenic molds and the severity of foliar disease, in 5 plots of 10 m x 50 m of 100 timber seedlings, coming from a middle terrace forest of the Arboretum - CIEFOR, Puerto Almendras in 2022, in the dry season (August, September and October) and wet season (February, March and April). For the collection of the sample, sterile envelopes were used, where the leaves with signs and symptoms of spots and/or wilting were placed. These samples were transferred to the Mycology laboratory of the Faculty of Biological Sciences - UNAP, to proceed with the culture on potato dextrose agar, isolation of colonies and sowing in a humid chamber of molds that cause foliar disease, to then carry out the microscopic identification in the specialized unit of Microbiology of the Natural Resources Research Center - CIRNA. For the statistical analysis, inferential statistics were carried out, through a univariate and bivariate analysis. From 73 samples of diseased plants analyzed, it was possible to determine the presence of 8 species of Phytopathogenic molds such as Aspergillus niger, Curvularia lunata, Fusarium oxysporum, Fusarium solani, Geotrichum candidum, Pestalotiopsis sp, Mucor mucedo and Penicillum sp. Of which in the dry season the highest prevalence was Fusarium solani and the lowest prevalence was Geotrichum candidum. As for the wet season, the highest prevalence was Fusarium solani and Fusarium oxysporum, and the lowest prevalence was Pestalotiopsis sp.